2014
DOI: 10.1080/14786419.2014.979423
|View full text |Cite
|
Sign up to set email alerts
|

Natural product extracts of the Canadian prairie plant,Thermopsis rhombifolia,have anti-cancer activity in phenotypic cell-based assays

Abstract: Many plant species within the terrestrial ecological zones of Canada have not yet been investigated for anti-cancer activity. We examined the scientific literature describing the endemic flora from the prairie ecological zone and selected the species, Thermopsis rhombifolia, locally known as the buffalo bean, for investigation of its anti-cancer potential. We tested it in cell-based assays using phenotypic screens that feature some of the hallmarks of cancer. An ethanolic extract prepared from T. rhombifolia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Utilization of the native legume Thermopsis rhombifolia (Nutt. ex Pursh) Richardson is also being investigated for medical purposes such as anticancer effects in humans (Kerneis et al 2015). The relevance of native perennial bromegrass as forage has been emphasized (Cayouette et al 1997).…”
Section: National Germplasm Collectionsmentioning
confidence: 99%
“…Utilization of the native legume Thermopsis rhombifolia (Nutt. ex Pursh) Richardson is also being investigated for medical purposes such as anticancer effects in humans (Kerneis et al 2015). The relevance of native perennial bromegrass as forage has been emphasized (Cayouette et al 1997).…”
Section: National Germplasm Collectionsmentioning
confidence: 99%
“…U2OS cells were either not treated or treated with a range of concentrations of PP-630F, then exposed to ambient light and observed by phasecontrast microscopy. In parallel, U2OS cells were treated with extract PP-120, prepared in a similar manner as that of PP-630F from a previously characterized prairie plant species, Thermopsis rhombifolia [3] (Figure 4A). Not-treated cells and PP-120-treated cells did not acquire vacuoles, as expected, whereas cells treated with PP-630F had light-induced vacuoles in a dose dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…We are investigating plants from the prairie ecological zone to discover new cell biology tools with which to study how human cells function. We have previously reported that extracts prepared from several prairie plant species, including Thermopsis rhombifolia that induced a cell cycle arrest identified by phenotypic assays [3,9]. Here, we identified extracts prepared from Symphoricarpos occidentalis (Caprifoliaceae) that induce a striking cellular phenotype when applied to human cells.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We have previously reported that extracts prepared from the prairie plant species, T. rhombifolia, were toxic to human cells and induced a cell cycle arrest [10].…”
Section: Introductionmentioning
confidence: 99%